The evolving personal, professional and physical impact on healthcare professionals during three COVID-19 waves: A cross-sectional study. (3rd September 2022) - Seys, Deborah; Peeters, Bart; Doggen, Kris; Vanhaecht, Kris
Abstract: Background: The COVID-19 pandemic has led to huge pressure on not only healthcare systems, but also on healthcare professionals. Objective: As the pandemic continues, the aim of this study is to evaluate how 10 reactions of healthcare professionals evolved during the first 18 months of COVID-19. Methods: A repeated cross-sectional study was performed with eight measurement points between April 2020 and September 2021 in Belgium. Participants were asked how frequently (on a scale of 0–10) they experienced positive and negative reactions during normal circumstances and during past week, referred to as before and during COVID-19, respectively. These reactions were stress, fatigue, difficulty sleeping, muscle strain, hypervigilance, leaving profession, headache, doubting knowledge and skills, flashbacks and fear. Results: In total, 13 308 respondents were included in our study. During both the first (March 2020) and second COVID-19 peak (November 2020), the measured personal, professional and physical reactions were significantly higher compared to before COVID-19. The third wave in April 2021 was shorter and less severe with regard to hospital admissions and deaths, yet an important impact on healthcare professionals could still be observed. 'Fatigue, ' 'stress, ' 'difficulty sleeping' and 'muscle strain' are the most worrying reactions in September 2021, which are increasing compared to the previous measurements. Conclusion: Our results showed that acute stress reactions decreased over time but that chronic stress reactions and professional reactions, such as 'intent to leave, ' increased. Healthcare organizations and policy makers should realize that 18 months after the start of COVID-19 almost all of the measured reactions continue to be more prevalent than before COVID-19. Moreover, the continuous increase over the last three measurement periods of the number of healthcare professionals who want to leave their profession is alarming. Continuous follow-up of the personal, professional and physical reactions is more than necessary.